Pembelajaran Pendidikan Agama Islam Cooperative Learning Di Sekolah Dasar - Afif Syaiful Mahmudin (STAI Sufyan Tsauri Majenang, 2021)
The learning model is a pattern designed as a reference in carrying out classroom learning. Arends said that the learning model is based on the approach used which is accompanied by various objectives, phases, situations and conditions in the classroom itself. PAI learning in schools is limited to memorizing concepts and materials without internalizing knowledge that can stick for a long time in each student. Moreover, conventional methods are still a mainstay for PAI teachers at the elementary level. Seeing from this reality, teachers feel the need to use a cooperative learning model that can increase students' creativity and academic understanding through fun ways. One of them is by applying the Cooperative Learning model. The characteristics of the cooperative learning method are working as a team or group based on cooperative management, the ability to work together and the skills to collaborate with fellow students. Slavin divides several cooperative learning models into three categories, namely 1) Student Teams Learning methods, which consist of Student Team-Achievement Divisions (STAD), Teams-Games-Tournaments (TGT) and Jigsaw II (JIG II). 2) Supported Cooperative learning methods, which consist of Learning Together-Circle (LT) of Learning (CL) and Cooperative Integrated Reading and Composition (CIRC). 3) Informal methods, consisting of Numbered Heads Together (NTH) and Think-Pair-share (TPS).